Metody matematyczne w procesie zarządzania ryzykiem rynkowym - Kuziak, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper discusses mathematical methods in market risk management process. First of all, the general introduction to market risk management process is given. Then the author divides group of mathematical models in two categories: analytical and simulation (deterministic, stochastic) models. Very briefly analytical and simulation models on each stage of the management process are presented. Some examples of literature for each models group are cited. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 331-341